Modeling of nonlinear processes of nucleation and growth of GaSxSe1–x (0 ≤ х ≤ 1) solid solutions - Asadov, S.M. (KU Publ., 2021)
The results on the study of modeling and physico-chemical study of the kinetics of nucleation and growth of GaSxSe1–x (0 ≤ х ≤ 1) solid solution. The nucleation heterogeneous process and growth of GaSxSe1–x crystals have been studied and simulated taking into account nonlinear equations considering the kinetic behavior of crystallizing phases. GaSxSe1–x single and nanocrystals were grown from solution, melt, and by chemical transport reaction through steam. GaSxSe1–x crystals were grown by chemical transport reaction in a two-temperature gradient furnace in a sealed quartz ampoule. Iodine was used as a transporting additive. Using the Fokker–Planck equation, the evolution of the distribution function of crystals of solid solutions of the GaS– GaSe system by size at the nucleation time is studied by a numerical method. For the convenience of comparing theory with experimental data, we used the GaS1–xSex (x = 0.7 molar fraction of GaSe) composition of the solid solution. The Monte Carlo method is used to approximate the time evolution of the nucleation of two types of particles for the GaS0.3Se0.7 solid solution, simulated by a constant nucleus size. The results of modeling nonlinear crystallization processes are consistent with experimental data.
GaSxSe1–x (0 ≤ х ≤ 1) қатты ерітіндісінің ядролануы мен өсуінің сызықтық емес процестерін модельдеу
Моделирование нелинейных процессов зарождения и роста твердых растворов GaSxSe1–x (0 ≤ х ≤ 1)
Keywords: nonlinear modeling; kinetics equation of crystallization; semiconductor GaS1–xSex; solid solutions; numerical solution algorithm; finite-difference equations; finite-difference equations; Fokker–Planck equation; evolution of the distribution function; Monte Carlo method